Glutathione reductase mediates drug resistance in glioblastoma cells by regulating redox homeostasis. Issue 1 (5th December 2017) - Zhu, Zhongling; Du, Shuangshuang; Du, Yibo; Ren, Jing; Ying, Guoguang; Yan, Zhao
Abstract: Glutathione (GSH) and GSH‐related enzymes constitute the most important defense system that protects cells from free radical, radiotherapy, and chemotherapy attacks. In this study, we aim to explore the potential role and regulatory mechanism of the GSH redox cycle in drug resistance in glioblastoma multiforme (GBM) cells. We found that temozolomide (TMZ)‐resistant glioma cells displayed lower levels of endogenous reactive oxygen species and higher levels of total antioxidant capacity and GSH than sensitive cells. Moreover, the expression of glutathione reductase (GSR), the key enzyme of the GSH redox cycle, was higher in TMZ‐resistant cells than in sensitive cells. Furthermore, silencing GSR in drug‐resistant cells improved the sensitivity of cells to TMZ or cisplatin. Conversely, the over‐expression of GSR in sensitive cells resulted in resistance to chemotherapy. In addition, the GSR enzyme partially prevented the oxidative stress caused by pro‐oxidant L‐buthionine ‐sulfoximine. The modulation of redox state by GSH or L‐buthionine –sulfoximine regulated GSR‐mediated drug resistance, suggesting that the action of GSR in drug resistance is associated with the modulation of redox homeostasis. Intriguingly, a trend toward shorter progress‐free survival was observed among GBM patients with high GSR expression. These results indicated that GSR is involved in mediating drug resistance and is a potential target for improving GBM treatment. Abstract : Glioblastoma multiforme is the most aggressive type of brain tumor. We show that glutathione reductase (GSR), the key enzyme of the glutathione (GSH) redox cycle, mediates drug resistance by regulating redox homeostasis and is a potential target for improving GBM treatment. These findings provide new ideas and strategies for reversing drug resistance.